ANMCO POSITION PAPER: The reorganization of cardiology in times of the SARS-CoV-2 pandemic. (26th August 2021) - Caldarola, Pasquale; Murrone, Adriano; Roncon, Loris; Di Pasquale, Giuseppe; Tavazzi, Luigi; Amodeo, Vincenzo; Aspromonte, Nadia; Cipriani, Manlio; Di Lenarda, Andrea; Domenicucci, Stefano; Francese, Giuseppina Maura; Imazio, Massimo; et al.
Abstract: The COVID-19 pandemic represents an unprecedented event that has brought deep changes in hospital facilities with reshaping of the health system organization, revealing inadequacies of current hospital and local health systems. When the COVID-19 emergency will end, further evaluation of the national health system, new organization of acute wards, and a further evolution of the entire health system will be needed to improve care during the chronic phase of disease. Therefore, new standards for healthcare personnel, more efficient organization of hospital facilities for patients with acute illnesses, improvement of technological approaches, and better integration between hospital and territorial services should be pursued. With experience derived from the COVID-19 pandemic, new models, paradigms, interventional approaches, values and priorities should be suggested and implemented.